Path to Peace : Fresh Hope for the World ; Dramatic Explorations by Gabriel Marcel. - Marcel, Gabirel (Marquette studies in philosophy., 2007)
This volume offers five plays by Gabriel Marcel, a multi-talented playwright, dramatic and literary critic, and writer. The selection of plays provides examples of Marcel's concrete, direct dramatic approach to questions of interpersonal relations, love, family, commitment, and creative fidelity. Editor Hanley, a Marcel researcher and translator, also offers introductions to the plays in the form of interviews conducted by her editing assistant. Annotation ©2008 Book News, Inc., Portland, OR (booknews.com).